Cryptosporidium surrogate removal in pilot-scale rapid sand filters comprising anthracite, pumice or engineered ceramic granular media, and its correlation with turbidity. (April 2022) - Pang, Liping; Tham, Annabelle; Nilprapa, Panan; Cocker, Adrian; MacDonald, Philip; Adams, Richard; Robson, Beth; Wood, David; Ward, Vernon; Nokes, Chris
Abstract: Removal of Cryptosporidium protozoa by granular media filtration is a critical step in conventional multi-barrier drinking-water treatment, and turbidity is commonly used to monitor system performance. We assessed the efficiencies of 3 different filter media at removing a Cryptosporidium parvum surrogate comprising glycoprotein-coated 4.5 μm polystyrene microspheres, and evaluated the responses of turbidity levels to surrogate concentrations. Field trials were performed using pilot-scale rapid sand filters comprising anthracite, pumice or engineered ceramic sand, while simulating a typical water treatment plant's operational conditions. Data from 44 trials indicated that the surrogate's log10 reduction values (LRVs) based on the peak concentrations were >3 in 100%, 70% and 41% of the trials with the ceramic sand, pumice sand and anthracite filters, respectively. The LRVs achieved in the ceramic sand filter trials (4.44 ± 0.38) were significantly greater than those in the pumice sand (3.21 ± 0.30) and anthracite (3.01 ± 0.70) filter trials (P < 0.00001). Correlations (P < 0.05) between turbidity levels and surrogate concentrations were observed in 17%, 44% and 29% of 51 trials involving the ceramic sand, pumice sand and anthracite filters, respectively. At peak surrogate breakthrough, the filtered water contained hundreds to thousands of surrogate particles/L, but the turbidity levels were <0.1 NTU in 63% and 71% of the trials with pumice and anthracite filters, respectively. In contrast, despite the ceramic sand filter achieving LRVs >3 consistently, the peak turbidity levels exceeded 0.30 NTU in 17% of the trials. Our findings highlight the need to introduce supplementary tools alongside turbidity to monitor filter performance more sensitively. Graphical abstract: Unlabelled Image Highlights: Oocyst surrogate removal was compared in conventional and alternative filter media. Anthracite showed the greatest variation in glycoprotein-coated microsphere removal. Engineered ceramic sand achieved markedly greater surrogate removal. Pumice sand outperformed anthracite and ceramic sand regarding turbidity reductions. Filtrate turbidity levels did not reliably indicate surrogate concentrations.